Self-healing of dense asphalt concrete by two different approaches: electromagnetic induction and infrared radiation - Ajam, H.; Lastra-Gonzalez, P.; Gomez-Meijide, B.; Airey, Gordon; Garcia, Alvaro (ASTM International, 2017)
Self-healing of cracks in asphalt mixtures is a phenomenon that can be accelerated by reducing the viscosity of bitumen as it increases the capillarity flow through the cracks. One method to achieve this is by increasing temperature, which also produces a thermal expansion that contributes to the circulation of the bitumen through cracks. In the present paper, the healing performance of asphalt mixture heated using infrared heating to simulate the natural solar radiation, and induction heating, a new method to increase the temperature of asphalt pavements, were compared in terms of time and healing temperature. Healing was defined as the relationship between the 3-point bending strength of an asphalt beam before and after healing. The results show that both methods reach similar and satisfactory healing ratios at around 90 %. However, induction heating is more energy efficient because the effect is concentrated on the binder, instead of heating the whole mix. This can be translated into much shorter heating times to reach the same healing level. Finally, an optimum radiation energy was found, after which higher amounts of infrared radiation damage the properties of the healed material.